Teacher Research as Self-Study and Collaborative Activity (LEARNing Landscapes, 2015)
This article highlights two insightful methods for advancing teacher research: practitioner self-study in relation to a range of texts, with which to examine one’s educational landscape; and classroom interventions conceived as a Vygotskian activity, via teacher-researcher collaboration. Both approaches allow teachers and collaborating researchers to share individual expertise across institutional boundaries and engage in creative local action.
Keywords: teacher research; collaborative activity; self-study